Novel modified leucine and phenylalanine dipeptides modulate viability and attachment of cancer cells - Jorda, Radek; Magar, Pratibha; Hendrychová, Denisa; Pauk, Karel; Dibus, Michal; Pilařová, Eliška; Imramovský, Aleš; Kryštof, Vladimír (European journal of medicinal chemistry, 2020)
Here, we describe the synthesis and biological characterization of 32 novel phenylalanine and leucine dipeptides modified on both the N and C termini by salicylic acid and aromatic or alicyclic amines, respectively. All compounds displayed antiproliferative activity in the tested cancer cell lines and eight of the compounds exhibited single digit micromolar GI50 values. Treated cells rapidly detached from surface of tissue culture dishes and we found that focal adhesion kinase (FAK), p130CAS and paxillin, which are important regulators of cell adhesion, were dephosphorylated at Y397, Y410 and Y118, respectively. The most potent compound reduced proliferation in the HCT-116 cell line in a dose-dependent manner, as shown by a decrease in 5-bromo-2'-deoxyuridine incorporation into DNA. Furthermore, this compound increased the levels of several apoptotic markers, including activated caspases, and increased site-specific poly-(ADP-ribose)polymerase (PARP) cleavage.
Keywords: dipeptidy; Cell Survival; Apoptosis; Drug Screening Assays, Antitumor; HCT116 buňky; Humans; Dipeptide; Adhesion; Tumor Cells, Cultured; Dipeptides; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Detachment; Dose-Response Relationship, Drug; Antineoplastic Agents; Leucine; lidé; proliferace buněk; molekulární struktura; nádorové buňky kultivované; Molecular Structure; Cell Proliferation; Phenylalanine; screeningové testy protinádorových léčiv; protinádorové látky; vztah mezi dávkou a účinkem léčiva; HCT116 Cells; cytotoxicity; fenylalanin; viabilita buněk; leucin